Genome-wide screening of DNA methylation in bovine blastocysts with different kinetics of development - Ispada, Jessica; De Lima, Camila Bruna; Sirard, Marc-André; Fontes, Patrícia Kubo [UNESP]; Nogueira, Marcelo Fábio Gouveia [UNESP]; Annes, Kelly; Milazzotto, Marcella Pecora (Springer Nature, 2018)
Background: The timing of the first cell divisions may predict the developmental potential of an embryo, including its ability to establish pregnancy. Besides differences related to metabolism, stress, and survival, embryos with different speeds of development present distinct patterns of gene expression, mainly related to energy and lipid metabolism. As gene expression is regulated by epigenetic factors, and that includes DNA methylation patterns, in this study we compared the global DNA methylation profile of embryos with different kinetics of development in order to identify general pathways and regions that are most influenced by this phenotype. For this purpose, bovine embryos were in vitro produced using sexed semen (female), classified as fast (four or more cells) or slow (two cells) at 40 hpi and cultured until blastocyst stage, when they were analyzed. Results: Genome-wide DNA methylation analysis identified 11,584 differently methylated regions (DMRs) (7976 hypermethylated regions in fast and 3608 hypermethylated regions in slow embryos). Fast embryos presented more regions classified as hypermethylated distributed throughout the genome, as in introns, exons, promoters, and repeat elements while in slow embryos, hypermethylated regions were more present in CpG islands. DMRs were clustered by means of biological processes, and the most affected pathways were related to cell survival/differentiation and energy/lipid metabolism. Transcripts profiles from DM genes connected with these pathways were also assessed, and the most part disclosed changes in relative quantitation. Conclusion: The kinetics of the first cleavages influences the DNA methylation and expression profiles of genes related to metabolism and differentiation pathways and may affect embryo viability.
Keywords: Blastocyst; DNA methylation; Epigenetics; Kinetics of development